cotribution to the phytochimical study of cynodon dactylon l.harvested from el'oued region - benine chaima (Université of Eloued جامعة الشهيد حمه لخضر, 2020)
Our study focused on the research of the antioxidant and antimicrobial activity effect, as well as the evaluation of the cytotoxic effect of ethanolic extracts from the aerial part of Cynodon dactylon L (Poaceae family) extracted using two methods maceration assisted extraction (MAE) and ultrasound assisted extraction (UAE). The phytochemical tests realized have highlighted various secondary metabolites in the aerial part of the plant including saponosides, terpenes, alkaloids, reducing sugars, cardiac glycosides, flavonoids and polyphenols. The yields of crude extracts were 9.40% for the MAE extract and 12.52% for the UAE extract. The results of the estimation of the phenolic compounds showed that the extract obtained by MAE contains a high level of polyphenols and total flavonoids estimated by (42.14 ± 0.75 mg EAG / gE and 23.57 ± 0.78 Mg EQ / gE), compared to the extract obtained by the UAE, which estimated by (29.93 ± 0.14 mg EAG / gE and 13.53 ± 0.33 Mg EQ / gE). In contrast, the content of condensed tannins in the extract of UAE (19.34 ± 0.48 Mg EC/gE) is higher than the extract of MAE (15.99 ± 0.63 Mg EC/gE). The evaluation of the antioxidant activity, carried out by two methods (Trapping of the free radical DPPH and ferric reducing antioxidant power FRAP) revealed a considerable antioxidant response. the DPPH test revealed that the MAE extract represents the most active extract, with an IC50 =7.52 ± 0.037 mg / ml and followed by the UAE extract with an IC50 = 8.83 ± 0.032 mg / ml. The same for the FRAP test, with value of 15.83 ± 0.37 mg EAA / g for MAE extract, followed by the UAE extract with a value of 15.38 ± 0.12 mg EAA / g. The antibacterial activity was evaluated against four strains: Pseudomonas aeruginosa, Salmonella Typhimurium, Staphylococcus aureus and Bacillus cereus. Also the antifungal activity against two strains Aspergillus carbonarius and Aspergillus parasiticus. the results that we have reached show that all the strains targeted have high susceptibility to the two ethanolic extracts of Cynodon dactylon L. The evaluation of cytotoxicity against RBCs was carried, the results shown the non-toxic effect of C. dactylon extracts. Thus making it suitable for the preparation of drugs involved in the treatment of various diseases
biochimie
Keywords: Cynodon dactylon; phenolic compounds; antioxidant activity; antimicrobial activity; cytotoxicity; نبات النجم